Batteries: Selenium‐Doped Cathodes for Lithium–Organosulfur Batteries with Greatly Improved Volumetric Capacity and Coulombic Efficiency (Adv. Mater. 33/2017). Issue 33 (1st September 2017) - Zhou, Jinqiu; Qian, Tao; Xu, Na; Wang, Mengfan; Ni, Xuyan; Liu, Xuejun; Shen, Xiaowei; Yan, Chenglin
Abstract : A novel type of selenium‐doped organosulfur polymer cathode with four sulfur atoms and one selenium atom (as the doped heteroatom) in the confined structure is designed and synthesized, as described in article number1701294 by Tao Qian, Chenglin Yan, and co‐workers. The unique molecular structure through Se doping contributes greatly to the improved volumetric capacity and Coulombic efficiency for highly stable lithium organosulfur batteries.